2009
DOI: 10.1038/npp.2009.200
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Additive Effects of the CNR1 and FAAH Genes on Brain Response to Marijuana Cues

Abstract: Because previous work has highlighted the significance of the cannabinoid receptor 1 (CNR1) and fatty acid amide hydrolase (FAAH) genes with respect to cannabis dependence (CD), the present study sought to characterize the neural mechanisms that underlie these genetic effects. To this end, we collected DNA samples and fMRI data using a cue-elicited craving paradigm in 37 3-day-abstinent regular marijuana users. The participants were grouped according to their genotype on two single nucleotide polymorphisms (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 58 publications
(62 reference statements)
7
115
2
1
Order By: Relevance
“…A total of 110 participants consisting of 62 nonusing controls and 48 marijuana users were recruited through fliers and media advertisement in the Albuquerque, NM, metro area. We previously presented results on subgroups of these participants (8,23,24). Written informed consent was obtained from all participants in accordance with the Institutional Review Board (IRB) of The University of New Mexico.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 110 participants consisting of 62 nonusing controls and 48 marijuana users were recruited through fliers and media advertisement in the Albuquerque, NM, metro area. We previously presented results on subgroups of these participants (8,23,24). Written informed consent was obtained from all participants in accordance with the Institutional Review Board (IRB) of The University of New Mexico.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Eggan and Lewis demonstrated a higher density of CB1Rs in the cingulate cortex and associative prefrontal regions compared to primary sensory and motor cortices (2007). The anterior cingulate cortex (ACC) and orbitofrontal cortex (OFC), two key brain regions with high prevalence of CB1Rs (Eggan and Lewis 2007;Filbey et al 2010), play a cardinal role in information processing during decision-making tasks (Bechara et al 2000;Kennerley et al 2011). It has been shown that these two brain regions have partially dissociable roles in several dimensions of decision making (Khani 2014;Lee et al 2007;Rushworth et al 2007) which include the evaluation of the expected benefits as well as costs associated with each potential choice of action during a decision.…”
Section: Introductionmentioning
confidence: 99%
“…The G allele of the mu-opioid receptor (OPRM1) A118G variant has been associated with increased alcohol cue reactivity in regular and heavy drinkers (Filbey et al, 2008), an effect that may be reversed following treatment with the mu-opioid receptor antagonist naltrexone (Schacht et al, 2013). Cannabinoid receptor signaling may mediate the effects of alcohol on dopamine release on the ventral tegmental area (VTA; Pava and Woodward, 2012), and the CNR1 rs2023239 G allele, conferring increased cannabinoid receptor binding (vs A allele), is associated with enhanced drug cue reactivity in regular alcohol drinkers as well as cue reactivity in regular marijuana users (Filbey et al, 2010). Variation in CNR1 may also impact nicotine dependence (Chen et al, 2008b), although to our knowledge this has not been examined in neuroimaging cue reactivity studies in smokers.…”
Section: Imaging Psychiatric Pharmacogenetics M Falcone Et Almentioning
confidence: 99%
“…Drinkers homozygous for this allele show increased reactivity to alcohol taste cues in the medial prefrontal cortex but decreased reactivity in the VTA; the apparently discordant findings across brain regions may reflect cue-evoked inhibitory responses in the VTA (Kareken et al, 2010). Of relevance to marijuana use, fatty acid amide hydrolase (FAAH) metabolically inactivates the endogenous cannabinoid anandamide; the A allele of the FAAH variant rs324420 is associated with lower risk of cannabis dependence (Tyndale et al, 2007) and reduced responses to marijuana tactile cues in regular cannabis users (Filbey et al, 2010). In the context of nicotine dependence, homozygosity for the G allele of the alpha-5 subunit of the nicotinic acetylcholine receptor gene (CHRNA5) rs16969968, which may increase nicotinic acetylcholine receptor activation (Bierut et al, 2008), is associated with enhanced cue reactivity in several cortical and subcortical brain regions in nicotine-dependent women (Janes et al, 2012).…”
Section: Imaging Psychiatric Pharmacogenetics M Falcone Et Almentioning
confidence: 99%